The Effect of Work Motivation and Career Development on Employee Job Satisfaction PT Indosato Jaya Makmur - Ibrahim Sevin Kurnia; Joko Ariawan (Yayasan Gema Bina Nusantara, 2023)
This research was conducted to determine the effect of work motivation and career development on employee job satisfaction. This research aims to analyze how much influence work motivation and career development have on employee job satisfaction, partially, jointly, or simultaneously. This research uses a quantitative method by distributing questionnaires to a research sample of 50 employees. The results of the t-test research on work motivation and employee job satisfaction are based on t-count results of 2.929 > t-table 1.677, and the career development t-test on employee job satisfaction is based on t-count results of 6.933 > t-table 1.677. So there is a partially significant influence between work motivation and employee job satisfaction and career development on employee job satisfaction. Meanwhile, based on the results of the F test, the influence of work motivation and career development on employee job satisfaction is based on the results of f-count 129.789 > f-table 4.05.